Language And Symbol In The Works Of Al-Jīlī: A Semiotic And Semantic Study - Miftahur Rahman (Eduvest - Journal of Universal Studies, 2025)
The tradition of shalawat in the context of the Malay Islamic archipelago is a cultural phenomenon that is rich in semiotic meaning and plays a significant role in the religious expression and construction of the collective identity of the Muslim community. This research aims to analyze the semiotic elements contained in the Malay prayer tradition, explore the symbolism that reflects spiritual and cultural values, and examine the role of this tradition in strengthening Islamic identity in the archipelago. The research method used is a literature study with a qualitative descriptive approach, analyzing prayer texts such as Barzanji, Diba', and Marhaban through the framework of cultural semiotics. The results of the study show that the shalawat tradition contains three main categories of semiotic signs, namely linguistic, symbolic, and performative that interact with each other to form a complex spiritual and cultural communication system. The linguistic dimension features a harmonious acculturation of Arabic and Malay, the symbolic dimension through visual and audio elements creates the identity of the Malay Muslim community, while the performative dimension strengthens social solidarity through collective rituals. The symbolic meaning of prayer includes three dimensions, namely spiritual as an expression of love for the Prophet Muhammad (PBUH), culture as the integration of local values with Islamic teachings, and social as a medium to strengthen community cohesion. The Malay shalawat tradition proves the flexibility of Islam Nusantara in accommodating local wisdom while maintaining the substance of religious teachings, creating an inclusive and contextual form of Islam.